Penggunaan Website Dan Media Sosial Dalam Membangun Citra Positif Perguruan Tinggi - Yosua Jefri Apriananta; Lina Sinatra Wijaya (Fakultas Ilmu Komunikasi UKWMS, 2018)
Having a positive image is an achievement for companies and organizations including a university. As a Public Relations (PR), building image both internally or externally is part of Public Relations’ job. In building the image, Online media and social media are really needed. Online media and social media are the communication media that are used by PR in order to improve or regain the positive image of the university. The purpose of this research is to find out whether using online media and social media can build positive image of the university or not. This research is a descriptive qualitative research, by using interviews, observation, and documentation for getting the data. This research uses Satya Wacana Christian University – Salatiga (UKSW) as the case study. The results of this research indicate that the use of Online media and social media in universities significantly influences the positive image, that is UKSW as a university with various ethnics and achievements, so it affected and educated the community. From the information, the communities can assess whether the universities have high quality, strong tolerance and cultured or not. Through online media and social media, trust also emerges from the communities, and this will positively affect the positive image of the university.